2015
DOI: 10.1097/prs.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Using an Absorbable Mesh in One-Stage Immediate Breast Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
(42 reference statements)
0
20
0
5
Order By: Relevance
“… 16 In 2015, Ganz et al published a study comparing direct-to-implant reconstruction using either a submuscular pocket (46 breasts) or a partial subpectoral pocket with Vicryl mesh extension (115 breasts), and found that use of absorbable mesh was superior to total submuscular coverage, along with a low complication rate and low revision rate. 17 A systematic review in 2015 of the peer-reviewed literature on breast reconstruction with Vicryl mesh showed a low complication rate and significant cost savings. 18 Recently, prepectoral reconstruction has been performed with nonabsorbable mesh, with success (2018).…”
Section: Discussionmentioning
confidence: 99%
“… 16 In 2015, Ganz et al published a study comparing direct-to-implant reconstruction using either a submuscular pocket (46 breasts) or a partial subpectoral pocket with Vicryl mesh extension (115 breasts), and found that use of absorbable mesh was superior to total submuscular coverage, along with a low complication rate and low revision rate. 17 A systematic review in 2015 of the peer-reviewed literature on breast reconstruction with Vicryl mesh showed a low complication rate and significant cost savings. 18 Recently, prepectoral reconstruction has been performed with nonabsorbable mesh, with success (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the formation of a new tissue layer, whose cells grow out through the pores of the mesh implant are surrounded by patients' own tissue. The frequency of postoperative complications when performing onestep breast reconstruction after subcutaneous mastectomy with mesh implant and silicone implant is not higher than the one observed during other types of reconstruction [33][34][35], which allows to implement this method.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common cancer among women 1 . According to the World Health Organization (WHO), more than 1,050,000 new cases occur per year worldwide.…”
Section: Introductionmentioning
confidence: 99%